Clinical profile of low-birth-weight neonates admitted in NICU: a tertiary care hospital-based study - Gargi H. Pathak; Anuya V. Chauhan; Dhara K. Gosai; Maulik Kumar R. Patel (International Journal of Contemporary Pediatrics, 2023)
Background: LBW is defined as weight at birth less than 2.5kg irrespective of gestational age. LBW neonate remains at much higher risk of morbidity and mortality than normal birth weight baby. Morbidity and mortality among LBW babies are a major health problem in our country, so it’s important to identify risk factors. Methods: A prospective observational study was conducted on 153 extramural LBW neonates admitted in Neonatal intensive care unit of civil hospital, BJ medical college Ahmedabad from April 2021 to January 2022. Results: Out of 153 neonates, 94 (61.4%) were preterm, appropriate for gestational age and 59 (38.6%) were small for gestational age including 41 (26.8%) term and 18 (11.8%) preterm. 16 (10%) were extremely LBW neonates and 28 (18%) were very low birth weight neonates. 77 (53%) neonates were late preterm and term gestational age. Most common indication of NICU admission was respiratory distress syndrome in 53 (27.8%) followed by sepsis 35 (18.4%), neonatal hyperbilirubinemia 22 (11.6%), birth asphyxia 15 (7.8%) and prematurity+LBW 16 (8.4%). Conclusions: Majority of LBW babies were preterm AGA babies. Respiratory distress syndrome, sepsis, birth asphyxia, prematurity and neonatal hyperbilirubinemia are major causes of admission. While, Respiratory distress syndrome, sepsis and birth asphyxia were common causes of expires. Respiratory distress syndrome is most common cause of morbidity and mortality in low-birth-weight babies. Appropriate and effective use of oxygen delivery system, surfactant, safe, early and effective transportation of neonates should be advised.